EDOEB recommandation_du9fevrier2017ofspdocumentsrelatifsalaugmentation vom 9. Februar 2017 - EDÖB (2017)
Recommandation du 9 février 2017: OFSP / Documents relatifs à l’augmentation des primes 2014-17